Drugs for the treatment of ulcerative colitis on the pharmaceutical market of Ukraine - L. M. Palchak; O. S. Kukhtenko; V. M. Khomenko (The State Expert Center of the Ministry of Health of Ukraine, 2023)
The prevalence of diseases of the digestive organs at the current stage of human development is extremely high, and their universally increasing incidence rate is estimated as an epidemic. In Ukraine, mortality from diseases of the digestive organs ranks fourth in the population mortality structure (after diseases of the circulatory system, neoplasms, and accidents). Among all diseases of digestive organs in the modern world, inflammatory bowel diseases are one of the most serious and unsolved problems in modern gastroenterology and coloproctology. In terms of morbidity, non-specific ulcerative colitis (UC) and Crohn's disease (CD) are inferior to other gastroenterological diseases, although in terms of the severity of the course, the frequency of complications and mortality, they occupy one of the leading places in the structure of diseases of the gastrointestinal tract. Therefore, the goal of our work was the marketing analysis of drugs for the treatment of non-specific ulcerative colitis containing mesalazine as an active component. Obtaining data on the demand on the pharmaceutical market for medicinal products with mesalazine, determining trends in the use of dosage forms with this substance will allow predicting approaches to the development of a domestic effective medicinal product containing mesalazine. The objects of the study were medicinal products of local and systemic action, containing mesalazine in their composition. To achieve the goal, generally accepted research methods were used, which contributed to the objective assessment of the analysis of the pharmaceutical market. The analysis of the assortment of medicines with mesalazine presented on the domestic pharmaceutical market was carried out according to the data of the classification system of the ATС, the State Formulary of Medicines, the State Register of Medicines of Ukraine. The presence on the pharmaceutical market of Ukraine of drugs of the group A07E Intestinal antiinflammatory agents indicates that the leader in terms of assortment offers is drugs with mesalazine (5-ASA). As of February 2023, Ukraine has registration certificates for 19 medicinal products of five brands with the active ingredient mesalazine. According to the received data, no medicinal product of domestic production containing mesalazine has been registered on the pharmaceutical market of Ukraine. Several types of dosage forms with mesalazine are available on the pharmaceutical market of Ukraine (coated tablets, long-acting granules, suppositories, and rectal suspension). It should be noted the absence of combined medicines with mesalazine. Also, there is no such medicinal form as enteric-dissolving hard gelatin capsules on the pharmaceutical market of Ukraine. Taking into account the obtained data, approaches to the introduction into production of a domestic medicinal product for the treatment of non-specific ulcerative colitis containing mesalazine and medicinal plant raw materials are in demand for pharmaceutical development.